2022
DOI: 10.1002/ente.202200217
|View full text |Cite
|
Sign up to set email alerts
|

4‐Hydrazinobenzoic‐Acid Antioxidant for High‐Efficiency Sn–Pb Alloyed Perovskite Solar Cells

Abstract: Partial tin replacement of lead is expected to be an effective means to fine-tune the bandgap of Sn-Pb alloyed lead-halide perovskite to harvest near-infrared light and thus further increase the efficiency of solar cells based on it, in particular for use as a bottom component cell in the tandem cell design to break through the theoretical Shockley-Queisser (S-Q) limit of the single-junction solar cells. However, the efficiency of Sn-Pb alloyed perovskite solar cells (PSCs) is still lower than expected owing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Recently, Li et al have demonstrated the use of reducing agents, such as 4-hydrazinobenzoic acid (HBA), with a hydrazine group as additives to enhance the performance of mixed Pb−Sn PSCs. 124 The introduction of the HBA additive stabilized the FA 0.5 MA 0.5 Pb 0.5 Sn 0.5 I 3 precursor solution without any color change. Fourier transform infrared (FTIR) spectra as displayed in Figure 2d indicated that the coordination bonds were formed between the amino/carboxyl groups of HBA and SnI 2 /PbI 2 in perovskite precursor solutions.…”
Section: Advances In Additive Engineering For Mixed Pb−sn Narrow-band...mentioning
confidence: 98%
See 3 more Smart Citations
“…Recently, Li et al have demonstrated the use of reducing agents, such as 4-hydrazinobenzoic acid (HBA), with a hydrazine group as additives to enhance the performance of mixed Pb−Sn PSCs. 124 The introduction of the HBA additive stabilized the FA 0.5 MA 0.5 Pb 0.5 Sn 0.5 I 3 precursor solution without any color change. Fourier transform infrared (FTIR) spectra as displayed in Figure 2d indicated that the coordination bonds were formed between the amino/carboxyl groups of HBA and SnI 2 /PbI 2 in perovskite precursor solutions.…”
Section: Advances In Additive Engineering For Mixed Pb−sn Narrow-band...mentioning
confidence: 98%
“…(d) FTIR spectra of HBA, PbI 2 –HBA, and SnI 2 –HBA. This panel was reproduced with permission from ref . Copyright 2022 Wiley-VCH.…”
Section: Advances In Additive Engineering For Mixed Pb–sn Narrow-band...mentioning
confidence: 99%
See 2 more Smart Citations
“…To surmount these issues, various reductants (e.g., metallic tin, [12] hypophosphorous acid, [13] 4-hydrazinobenzoic acid, [14,15] and Hydrazine [16] ) and antioxidants (e.g., hydroxybenzene sulfonic acid, [17] gallic acid, [18] and ascorbic acid [19] ) have been introduced to restrain the oxidation reaction and retard the crystallization process, aiming to enable large grain size and a stoichiometric crystal lattice devoid of vacancies. Nevertheless, in addition to the external oxidative factor, the oxidation of Sn 2+ may be initiated by lattice instability associated with the internal defect equilibrium.…”
Section: Introductionmentioning
confidence: 99%